Carbon negative electrode material and preparation method thereof, negative electrode sheet, secondary battery and electric device
Patent Information
- Application Number
- CN202611173986.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0002]生物质碳因成本低、来源广,可以被用作电池中的负极材料,但传统技术中的生物质碳用于电池负极时,存在以下问题:(1)电压滞后,传统硬碳嵌钠电位<1.4V,易引发析氢;(2)扩散缓慢,无序孔道导致离子扩散系数<10-10cm2/s;(3)掺杂不均,传统氮掺杂工艺吡啶氮占比<40%,储钠活性位不足
[0038](1)电压提升:吡啶氮诱导高储钠电位,电位至1.52V~1.58V。
Smart Images

Figure CN122889755A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to carbon anode materials and their preparation methods, anode sheets, secondary batteries, and electrical devices. Background Technology
[0002] Biomass carbon is used as a negative electrode material in batteries due to its low cost and wide availability. However, when biomass carbon is used as a negative electrode in batteries in traditional technologies, the following problems exist: (1) voltage lag, the sodium intercalation potential of traditional hard carbon is <1.4V, which easily leads to hydrogen evolution; (2) slow diffusion, the disordered channels result in an ion diffusion coefficient <10. -10 cm 2 / s; (3) Uneven doping, the proportion of pyridine nitrogen in traditional nitrogen doping process is <40%, and the sodium storage active sites are insufficient. Summary of the Invention
[0003] Therefore, it is necessary to provide a carbon anode material that achieves improved sodium intercalation potential, high diffusion coefficient, and uniform doping.
[0004] One embodiment of this application provides a carbon anode material.
[0005] A carbon anode material, wherein the porous structure includes micropores, mesopores, and macropores, the volume ratio of the micropores, mesopores, and macropores is (1.5~2):(2.5~2):1, the pore size of the micropores is less than 2 nm, the pore size of the mesopores is 2 nm~50 nm, and the pore size of the macropores is greater than 50 nm; the total nitrogen content in the carbon anode material is 4 at%~5.5 at%, and the nitrogen content in pyridine nitrogen accounts for greater than or equal to 55% of the total nitrogen content.
[0006] In some embodiments, the specific surface area of the carbon anode material is 1000 m². 2 / g~1200m 2 / g.
[0007] One embodiment of this application provides a method for preparing a carbon anode material.
[0008] A method for preparing a carbon anode material includes the following steps:
[0009] Lignin removal treatment of sisal fibers;
[0010] The sisal fibers after lignin removal treatment were subjected to hydrothermal carbonization to obtain a first intermediate.
[0011] The first intermediate was subjected to oxygen-limited pyrolysis to obtain the second intermediate;
[0012] The second intermediate was subjected to acid activation treatment to obtain the third intermediate;
[0013] Furthermore, the third intermediate is subjected to nitrogen doping enhancement treatment.
[0014] In some of these embodiments, the process of removing lignin from sisal fibers includes the following steps:
[0015] The sisal fibers were placed in an alkaline solution and treated with alkali at a temperature of 80℃~100℃ for 2h~4h.
[0016] The sisal fibers after alkali treatment are then washed with water.
[0017] In addition, the sisal fibers after water washing are dried.
[0018] In some embodiments, the alkaline solution includes at least one of the following: 5wt%~8wt% NaOH solution, 5wt%~10wt% KOH solution, 3wt%~6wt% LiOH solution, 8wt%~12wt% Na2CO3 solution, 8wt%~12wt% K2CO3 solution, and 10wt%~20wt% ammonia solution.
[0019] In some embodiments, the washing process satisfies the following condition: the aqueous solution containing the sisal fibers is washed until the pH value is 6.5 to 7.5.
[0020] In some embodiments, the drying process satisfies the following condition: the drying temperature is 60°C to 70°C.
[0021] In some of the embodiments, the hydrothermal carbonization treatment meets the following conditions: the solid-liquid ratio (g / mL) between the lignin-free sisal fiber and water is 1:(15~20), the hydrothermal carbonization temperature is 180℃~220℃, and the hydrothermal carbonization time is 1h~3h.
[0022] In some embodiments, the oxygen-limited pyrolysis treatment satisfies the following conditions: under a mixed atmosphere, the temperature is increased to 650°C to 750°C at a rate of 5°C / min to 10°C / min, and the oxygen-limited pyrolysis time is 0.5h to 2h. The mixed atmosphere includes oxygen and an inert gas, wherein the concentration of oxygen is 0.5vol% to 2vol.
[0023] In some of these embodiments, the inert gas flow rate is 50 mL / min to 60 mL / min.
[0024] In some of these embodiments, the inert gas includes argon.
[0025] In some embodiments, the acid in the acid activation treatment includes at least one of the following: 85wt%~95wt% phosphoric acid, 60wt%~75wt% sulfuric acid, 30wt%~65wt% nitric acid, 10wt%~20wt% hydrochloric acid, 20wt%~40wt% citric acid, and 20wt%~40wt% p-toluenesulfonic acid.
[0026] In some embodiments, the acid activation treatment satisfies the following conditions: the second intermediate is mixed with acid at a mass ratio of 1:(1.5~2.5), and activated at 850°C~950°C for 20min~60min in a protective atmosphere.
[0027] In some embodiments, the nitrogen doping enhancement treatment satisfies the following conditions: the third intermediate is placed in an atmosphere containing 4 vol% to 6 vol% NH3 and microwaved for 5 min to 10 min at a microwave power of 8 W / g to 12 W / g.
[0028] One embodiment of this application provides a negative electrode sheet.
[0029] A negative electrode sheet includes at least one of the carbon negative electrode materials described in any of the above embodiments and the carbon negative electrode materials prepared by the preparation method described in any of the above embodiments.
[0030] One embodiment of this application provides a secondary battery.
[0031] A secondary battery comprising the negative electrode sheet described in any of the above embodiments.
[0032] In some embodiments, the secondary battery includes a sodium-ion battery.
[0033] One embodiment of this application provides an electrical device.
[0034] An electrical device includes at least one of the following: the carbon negative electrode material described in any of the above embodiments, the carbon negative electrode material prepared by the preparation method described in any of the above embodiments, the negative electrode sheet described in any of the above embodiments, and the secondary battery described in any of the above embodiments.
[0035] The aforementioned carbon anode materials can achieve improved sodium intercalation potential, high diffusion coefficient, and high and uniform doping concentration.
[0036] In at least one embodiment, the sodium intercalation potential of the above-described gradient porous carbon anode material is greater than or equal to 1.5V, and the ion diffusion coefficient is greater than or equal to 10. -9 m 2 / s, carbon anode materials with a pyridine nitrogen content greater than or equal to 55%.
[0037] In at least one embodiment, the above-described carbon anode material has at least the following beneficial effects:
[0038] (1) Voltage boost: Pyridine nitrogen induces a high sodium storage potential, with the potential reaching 1.52V~1.58V.
[0039] (2) Rapid diffusion: The gradient pores enable an ion diffusion coefficient of 5×10⁻⁶. -9 m 2 / s.
[0040] (3) High cycle life: 5C rate 5000 cycles capacity retention rate >95%. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0042] To gain a more complete understanding of this application and its beneficial effects, the following description will be provided in conjunction with the accompanying drawings. In the following description, the same reference numerals denote the same parts.
[0043] Figure 1 This is a schematic diagram of the preparation method of the carbon anode material according to an embodiment of this application;
[0044] Figure 2 This is a schematic diagram of the hierarchical pore structure and nitrogen doping uniformity in Embodiment 1 of this application;
[0045] Figure 3 The image shows the BET pore structure and XPS N 1s peak distribution diagram in Embodiment 1 of this application.
[0046] Figure 4 This is a comparison chart of the key performance of Examples 1 to 3 of this application with Comparative Examples 1 to 10. Detailed Implementation
[0047] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0048] In the description of this application, "several" means one or more, "multiple" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.
[0049] In this document, "optionally," "optionally," and "optional" mean that something is optional, that is, it is selected from either "with" or "without." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "option" is independent. In this application, descriptions such as "optionally contains" and "optionally includes" indicate "contains or does not contain."
[0050] In this application, unless otherwise stated, the sum of the parts of each component in the composition may be 100 parts by weight. Unless otherwise specified, the percentages (including weight percentages) in this application are based on the total weight of the composition. In addition, "wt%" in this document means mass percentage and "at%" means atomic percentage.
[0051] In this document, unless otherwise stated, the reaction steps may be performed in the order described herein or not. For example, other steps may be included between reaction steps, and the order of reaction steps may be appropriately interchanged. This is something that those skilled in the art can determine based on conventional knowledge and experience. Preferably, the reaction methods described herein are performed sequentially.
[0052] In this application, when numerical intervals (i.e., numerical ranges) are mentioned, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0054] One embodiment of this application provides a carbon anode material to solve at least one of the following technical problems when biomass carbon is used as a battery anode in conventional technology: (1) voltage hysteresis, the sodium intercalation potential of conventional hard carbon is <1.4V, which easily leads to hydrogen evolution; (2) slow diffusion, the disordered channels result in an ion diffusion coefficient <10. -10 cm 2 / s; (3) Uneven doping, conventional nitrogen doping process has a pyridine nitrogen ratio of <40%, and insufficient sodium storage active sites. The carbon anode material will be explained below with reference to the attached figures.
[0055] The carbon anode material provided in one embodiment of this application is exemplary; please refer to [link to relevant documentation]. Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of a carbon anode material provided in one embodiment of this application. The carbon anode material of this application can be used to prepare the anode of a battery.
[0056] To more clearly illustrate the structure of carbon anode materials, the following description will be provided in conjunction with the accompanying drawings.
[0057] For example, please refer to Figure 1 As shown, a carbon anode material has a porous structure including micropores, mesopores, and macropores, with a volume ratio of (1.5~2):(2.5~2):1 between micropores, mesopores, and macropores. The pore size of the micropores is less than 2 nm, the pore size of the mesopores is 2 nm~50 nm, and the pore size of the macropores is greater than 50 nm. The total nitrogen content in the carbon anode material is 4 at%~5.5 at%, and the nitrogen content in pyridine nitrogen accounts for more than or equal to 55% of the total nitrogen content. For example, the total nitrogen content in the carbon anode material can be, but is not limited to: 4 at%, 4.1 at%, 4.2 at%, 4.3 at%, 4.4 at%, 4.5 at%, 4.6 at%, 4.7 at%, 4.8 at%, 4.9 at%, 5 at%, 5 at%, 5.1 at%, 5.2 at%, 5.3 at%, 5.4 at%, 5.5 at%, or any range between the two mentioned above.
[0058] The aforementioned carbon anode material can achieve increased sodium intercalation potential, high diffusion coefficient, and uniform doping. The aforementioned gradient porous carbon anode material has a sodium intercalation potential greater than or equal to 1.5V and an ion diffusion coefficient greater than or equal to 10. -9 m 2 / s, carbon anode materials with a pyridine nitrogen content greater than or equal to 55%.
[0059] In some embodiments, the pore size of the micropore is greater than or equal to 0.5 nm and less than 2 nm. For example, the pore size of the micropore includes, but is not limited to, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, or a range between any two of the foregoing.
[0060] In some embodiments, the aperture of the macropore is greater than 50 nm and less than or equal to 200 nm. For example, the aperture value of the macropore includes, but is not limited to: 55 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, or any range between the foregoing.
[0061] In some embodiments, the nitrogen element in pyridine nitrogen accounts for a proportion greater than or equal to 55% and less than or equal to 80% of the total nitrogen element. For example, the proportion of nitrogen element in pyridine nitrogen to the total nitrogen element includes, but is not limited to: 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, or any range between the foregoing.
[0062] In some of these embodiments, the specific surface area of the carbon anode material is 1000 m². 2 / g~1200m 2 / g. For example, the specific surface area of carbon anode materials includes, but is not limited to, 1000m². 2 / g, 1050m 2 / g、1100m 2 / g、1150m 2 / g、1200m 2 / g or any of the two mentioned above.
[0063] One embodiment of this application provides a method for preparing a carbon anode material.
[0064] A method for preparing a carbon anode material includes the following steps:
[0065] S10. The sisal fiber is subjected to lignin removal treatment.
[0066] S20. The sisal fibers after lignin removal are subjected to hydrothermal carbonization to obtain the first intermediate.
[0067] S30. Perform oxygen-limited pyrolysis on the first intermediate to obtain the second intermediate.
[0068] S40. The second intermediate is subjected to acid activation treatment to obtain the third intermediate.
[0069] S50. Nitrogen doping is applied to the third intermediate to enhance its strength.
[0070] In some of these embodiments, the process of removing lignin from sisal fibers includes the following steps:
[0071] S11. Place the sisal fiber in an alkaline solution and treat it with alkali at a temperature of 80℃~100℃ for 2h~4h.
[0072] S12. The sisal fibers after alkali treatment are washed with water.
[0073] S13. Dry the sisal fibers after washing.
[0074] In some of these embodiments, the alkaline solution includes at least one of the following: 5wt%~8wt% NaOH solution, 5wt%~10wt% KOH solution, 3wt%~6wt% LiOH solution, 8wt%~12wt% Na2CO3 solution, 8wt%~12wt% K2CO3 solution, and 10wt%~20wt% ammonia solution.
[0075] For example, the temperature conditions during alkali treatment include, but are not limited to: 80℃, 85℃, 90℃, 95℃, 100℃ or any two of the above; the treatment time during alkali treatment includes, but is not limited to: 2h, 2.5h, 3h, 3.5h, 4h or any two of the above.
[0076] In some embodiments, the washing process satisfies the following condition: the pH of the aqueous solution containing sisal fibers is 6.5 to 7.5. For example, during the washing process, the pH value of the aqueous solution containing sisal fibers may include, but is not limited to, 6.5, 6.7, 6.9, 7.0, 7.1, 7.3, 7.5, or any range between the foregoing.
[0077] In some embodiments, the drying process satisfies the following condition: the drying temperature is 60°C to 70°C. For example, the drying temperature may be, but is not limited to, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, or any range between the foregoing.
[0078] In some embodiments, the hydrothermal carbonization treatment meets the following conditions: the solid-liquid ratio (g / mL) between lignin-free sisal fiber and water is 1:(15~20), the hydrothermal carbonization temperature is 180℃~220℃, and the hydrothermal carbonization time is 1h~3h. For example, during hydrothermal carbonization, the solid-liquid ratio (g / mL) between lignin-free sisal fiber and water includes, but is not limited to: 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, or any range between the two; the hydrothermal carbonization temperature is greater than or equal to 180℃ and less than or equal to 220℃. For example, the hydrothermal carbonization temperature includes, but is not limited to: 180℃, 185℃, 190℃, 195℃, 200℃, 205℃, 210℃, 215℃, 220℃, or any range between the two; the hydrothermal carbonization time is greater than or equal to 1h and less than or equal to 3h. For example, the hydrothermal carbonization time can be, but is not limited to, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, or any range between the two mentioned above.
[0079] In some of these embodiments, hydrothermal carbonization is performed by placing the lignin-free sisal fibers in a reaction vessel.
[0080] In some embodiments, the oxygen-limited pyrolysis treatment meets the following conditions: under a mixed atmosphere, the temperature is increased to 650℃~750℃ at a rate of 5℃ / min~10℃ / min, and the oxygen-limited pyrolysis time is 0.5h~2h. The mixed atmosphere includes oxygen and an inert gas, wherein the oxygen concentration is 0.5vol%~2vol%. For example, during oxygen-limited pyrolysis, the heating rate includes, but is not limited to: 5℃ / min, 5.5℃ / min, 6℃ / min, 6.5℃ / min, 7℃ / min, 7.5℃ / min, 8℃ / min, 8.5℃ / min, 9℃ / min, 9.5℃ / min, 10℃ / min, or any range between the foregoing; during oxygen-limited pyrolysis, the temperature includes, but is not limited to: 650℃, 660℃, 670℃, 6... The temperature range is 80℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, or any two of the above. For oxygen-limited pyrolysis, the time value includes, but is not limited to: 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, or any two of the above.
[0081] In some of these embodiments, the first intermediate is placed in a tube furnace during the oxygen-limited pyrolysis process.
[0082] It should be noted that in this application, the oxygen-limited pyrolysis treatment is a process of pyrolyzing sisal fibers at medium and low temperatures under a strictly controlled atmosphere of small amounts of oxygen. Its core lies in "oxygen limitation," where the presence of oxygen at a concentration of 0.5 vol% to 2 vol% can trigger a series of complex cross-linking, oxidation, and partial pyrolysis reactions. At temperatures of 650℃ to 750℃, oxygen reacts with active sites in the fiber, such as H atoms, promoting intermolecular cross-linking and forming stable ether bonds, carbonyl groups, etc., thus building a robust "skeleton" before final high-temperature carbonization. This skeleton determines the porous structure of the final carbon anode material.
[0083] In some embodiments, the inert gas flow rate is 50 mL / min to 60 mL / min. For example, the inert gas flow rate may include, but is not limited to, 50 mL / min, 51 mL / min, 52 mL / min, 53 mL / min, 54 mL / min, 55 mL / min, 56 mL / min, 57 mL / min, 58 mL / min, 59 mL / min, 60 mL / min, or any range between the foregoing.
[0084] In some of these embodiments, the inert gas includes argon.
[0085] In some embodiments, the acid in the acid activation treatment includes at least one of the following: 85wt%~95wt% phosphoric acid, 60wt%~75wt% sulfuric acid, 30wt%~65wt% nitric acid, 10wt%~20wt% hydrochloric acid, 20wt%~40wt% citric acid, and 20wt%~40wt% p-toluenesulfonic acid.
[0086] In some embodiments, the acid activation treatment satisfies the following conditions: the second intermediate is mixed with acid at a mass ratio of 1:(1.5~2.5), and activated at 850°C~950°C for 20 min~60 min under a protective atmosphere. For example, the mass ratio of the second intermediate to phosphoric acid includes, but is not limited to: 1:1.5, 1:1.6, 1:7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, or any range between the foregoing. For example, the activation temperature includes, but is not limited to: 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, or any range between the foregoing. For example, the processing time for activation treatment may include, but is not limited to: 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 45 min, 48 min, 50 min, 51 min, 54 min, 55 min, 56 min, 58 min, 59 min, 60 min, or any range between the two mentioned above.
[0087] In some of these embodiments, the protective atmosphere is argon.
[0088] In some embodiments, the nitrogen doping enhancement treatment satisfies the following conditions: the third intermediate is placed in an atmosphere containing 4 vol% to 6 vol% NH3 and microwaved for 5 to 10 minutes at a microwave power of 8 W / g to 12 W / g. For example, the volume percentage of NH3 includes, but is not limited to: 4 vol%, 4.2 vol%, 4.4 vol%, 4.5 vol%, 4.6 vol%, 4.8 vol%, 5 vol%, 5.1 vol%, 5.2 vol%, 5.4 vol%, 5.6 vol%, 5.8 vol%, 6 vol%, or any range between the foregoing. For example, the microwave power includes, but is not limited to: 8 W / g, 8.5 W / g, 9 W / g, 9.5 W / g, 10 W / g, 10.5 W / g, 11 W / g, 11.5 W / g, 12 W / g, or any range between the foregoing. For example, the microwave processing time may include, but is not limited to, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, or any range between the two mentioned above.
[0089] One embodiment of this application provides a negative electrode sheet.
[0090] A negative electrode sheet includes at least one of the carbon negative electrode materials in any of the above embodiments and the carbon negative electrode materials prepared by the preparation methods in any of the above embodiments.
[0091] In some embodiments, the negative electrode sheet includes a composite current collector and a negative electrode film layer disposed on at least one side of the composite current collector, wherein at least one negative electrode film layer includes a core-shell carbon negative electrode material.
[0092] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto at least one side surface of the composite current collector, and then drying and compacting (compaction can be done by cold pressing) to obtain the negative electrode sheet.
[0093] One embodiment of this application provides a secondary battery.
[0094] A secondary battery, comprising the negative electrode sheet in any of the above embodiments.
[0095] In some of these implementations, the secondary battery includes a sodium-ion battery.
[0096] In some embodiments, the secondary battery includes the negative electrode sheet of this application, as well as a positive electrode sheet and a separator; wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0097] In this application, unless otherwise specified, the electrode sheet can be a positive electrode sheet or a negative electrode sheet. The "active material" in the electrode sheet refers to a material capable of reversibly inserting and extracting active ions. Unless otherwise specified, "negative electrode active material" refers to a material used in the negative electrode sheet capable of reversibly inserting and extracting active ions; "positive electrode active material" refers to a material used in the positive electrode sheet capable of reversibly extracting and inserting active ions. During charging of the secondary battery, active ions are extracted from the positive electrode and inserted into the negative electrode via the electrolyte; conversely, during discharging, active ions are extracted from the negative electrode and inserted into the positive electrode. The active ion is not particularly limited and can be lithium ions, in which case it corresponds to a lithium-ion secondary battery.
[0098] In this application, "active material" and "active substance" have the same meaning and can be used interchangeably; "positive electrode active substance" and "positive electrode active material" have the same meaning and can be used interchangeably; "negative electrode active substance" and "negative electrode active material" have the same meaning and can be used interchangeably.
[0099] One embodiment of this application provides an electrical device.
[0100] An electrical device includes at least one of the following: a carbon negative electrode material according to any of the above embodiments, a carbon negative electrode material prepared by the preparation method according to any of the above embodiments, a negative electrode sheet according to any of the above embodiments, and a secondary battery according to any of the above embodiments.
[0101] Secondary batteries can be used as a power source for the aforementioned electrical devices, or as an energy storage unit for these devices. Electrical devices can include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be, for example, mobile phones, laptops, etc.; electric vehicles can be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these. The secondary battery can be selected based on the usage requirements of the electrical device.
[0102] Example 1
[0103] This embodiment provides a carbon anode material.
[0104] The carbon anode material in this embodiment was prepared using the following method.
[0105] A method for preparing a carbon anode material includes the following steps:
[0106] S100, lignin removal treatment is performed on sisal fibers.
[0107] Sisal fibers were treated in a 6 wt% NaOH solution at 90°C for 3 hours.
[0108] Wash with water until the pH of the aqueous solution containing sisal fibers is 7.
[0109] Drying treatment at 65℃.
[0110] S200. The lignin-free sisal fiber is placed in a reaction vessel for hydrothermal carbonization to obtain the first intermediate. The solid-liquid ratio between the lignin-free sisal fiber and water is 1:18 (g / mL), the hydrothermal carbonization temperature is 200℃, and the hydrothermal carbonization time is 2h.
[0111] S300. The first intermediate is placed in a tube furnace, and argon gas at a flow rate of 55 mL / min is introduced. The temperature is increased to 700℃ at a rate of 8℃ / min, and oxygen-limited pyrolysis is performed for 1 hour to obtain the second intermediate.
[0112] S400. The second intermediate is mixed with 90wt% phosphoric acid at a mass ratio of 1:2 and activated at 900℃ for 30 min in an argon atmosphere to obtain the third intermediate by acid activation treatment.
[0113] S500. The third intermediate is placed in an atmosphere containing 5 vol% NH3 and microwaved for 8 min at a microwave power of 10 W / g to perform nitrogen doping enhancement treatment on the third intermediate.
[0114] Performance Characterization
[0115] (1) Structural analysis:
[0116] See Figure 2 , Figure 3 As shown, Figure 2 This is a schematic diagram of the hierarchical pore structure and nitrogen doping uniformity in Embodiment 1 of this application. Figure 3 The image shows the BET pore structure and XPS N 1s peak distribution diagram in Embodiment 1 of this application.
[0117] BET: Specific surface area 1150 m² / g, micropore:mesopore:macropore ratio 32%:51%:17%
[0118] XPS: N 1s spectrum shows that pyridine nitrogen (398.6 eV) accounts for 61.3%.
[0119] (2) Electrochemical performance:
[0120] Half-cell test (1M Na2SO4 electrolyte):
[0121] Sodium intercalation potential: 1.55V (0.1C).
[0122] 0.5C capacity: 305mAh / g.
[0123] Capacity retention after 5000 cycles at 5C rate: 96.7%.
[0124] (3) Diffusion kinetics
[0125] GITT test: Sodium ion diffusion coefficient 7.2 × 10⁻⁶ -9 cm 2 / s (0.5C).
[0126] Example 2
[0127] This embodiment provides a carbon anode material.
[0128] The carbon anode material in this embodiment was prepared using the following method.
[0129] A method for preparing a carbon anode material includes the following steps:
[0130] S100, lignin removal treatment is performed on sisal fibers.
[0131] Sisal fibers were treated in a 5 wt% NaOH solution at 80°C for 4 hours.
[0132] Wash with water until the pH of the aqueous solution containing sisal fibers is 7.
[0133] Drying treatment at 70℃.
[0134] S200. The lignin-free sisal fiber is placed in a reaction vessel for hydrothermal carbonization to obtain the first intermediate. The solid-liquid ratio between the lignin-free sisal fiber and water is 1:15 (g / mL), the hydrothermal carbonization temperature is 180℃, and the hydrothermal carbonization time is 3h.
[0135] S300. The first intermediate is placed in a tube furnace, and argon gas at a flow rate of 50 mL / min is introduced. The temperature is increased to 650℃ at a rate of 5℃ / min, and oxygen-limited pyrolysis is performed for 2 hours to obtain the second intermediate.
[0136] S400. The second intermediate is mixed with 85wt% phosphoric acid at a mass ratio of 1:1.8 and activated at 850℃ for 40 min in an argon atmosphere to obtain the third intermediate by acid activation treatment.
[0137] S500. The third intermediate is placed in an atmosphere containing 4 vol% NH3 and microwaved for 10 min at a microwave power of 8 W / g to perform nitrogen doping enhancement treatment on the third intermediate.
[0138] Performance Characterization
[0139] (1) Structural analysis:
[0140] BET: Specific surface area 1060 m² / g, micropore:mesopore:macropore = 34%:49%:17%;
[0141] XPS: N 1s spectrum shows a total nitrogen content of 4.2 at, with pyridine nitrogen (398.6 eV) accounting for 56.8%.
[0142] (2) Electrochemical performance:
[0143] Half-cell test (1M Na2SO4 electrolyte):
[0144] Sodium intercalation potential: 1.52V (0.1C).
[0145] 0.5C capacity: 292mAh / g.
[0146] Capacity retention after 5000 cycles at 5C rate: 95.4%.
[0147] (3) Diffusion kinetics
[0148] GITT test: Sodium ion diffusion coefficient 5.8 × 10⁻⁶ -9 cm2 / s (0.5C).
[0149] Example 3
[0150] This embodiment provides a carbon anode material.
[0151] The carbon anode material in this embodiment was prepared using the following method.
[0152] A method for preparing a carbon anode material includes the following steps:
[0153] S100, lignin removal treatment is performed on sisal fibers.
[0154] Sisal fibers were treated in an 8 wt% NaOH solution at 100°C for 2 hours.
[0155] Wash with water until the pH of the aqueous solution containing sisal fibers is 7.
[0156] Drying treatment at 60℃.
[0157] S200. The lignin-free sisal fiber is placed in a reaction vessel for hydrothermal carbonization to obtain the first intermediate. The solid-liquid ratio between the lignin-free sisal fiber and water is 1:20 (g / mL), the hydrothermal carbonization temperature is 220℃, and the hydrothermal carbonization time is 1h.
[0158] S300. The first intermediate is placed in a tube furnace, and argon gas is passed through it at a flow rate of 60 mL / min. The temperature is increased to 750℃ at a rate of 10℃ / min, and oxygen-limited pyrolysis is performed for 0.5 h to obtain the second intermediate.
[0159] S400. The second intermediate is mixed with 95wt% phosphoric acid at a mass ratio of 1:2.2 and activated at 950℃ for 20 min in an argon atmosphere to obtain the third intermediate by acid activation treatment.
[0160] S500. The third intermediate is placed in an atmosphere containing 6 vol% NH3 and microwaved for 10 min at a microwave power of 12 W / g to perform nitrogen doping enhancement treatment on the third intermediate.
[0161] Performance Characterization
[0162] (1) Structural analysis:
[0163] BET: Specific surface area 1185 m² 2 / g, Micropore:Mesopore:Macropore = 30%:53%:17%;
[0164] XPS: N 1s spectrum shows a total nitrogen content of 5.3 at, with pyridine nitrogen (398.6 eV) accounting for 63.8%.
[0165] (2) Electrochemical performance:
[0166] Half-cell test (1M Na2SO4 electrolyte):
[0167] Sodium intercalation potential: 1.57V (0.1C).
[0168] 0.5C capacity: 298mAh / g.
[0169] Capacity retention after 5000 cycles at 5C rate: 96.1%.
[0170] (3) Diffusion kinetics
[0171] GITT test: Sodium ion diffusion coefficient 6.9 × 10⁻⁶ -9 cm 2 / s (0.5C).
[0172] Comparative Example 1
[0173] This comparative example provides a negative electrode material.
[0174] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 1, except that step S200 is omitted in this comparative example.
[0175] Analysis showed that the pyridine nitrogen content was 38.0%, the sodium intercalation potential was 1.42V, and the capacity retention rate after 5000 cycles at 5C was 78.5%.
[0176] Comparative Example 2
[0177] This comparative example provides a negative electrode material.
[0178] The negative electrode material in this comparative example is basically the same as that in Example 1. The difference is that in this comparative example, the S500 step adopts the traditional technique of pyrolytic nitrogen doping, that is, pyrolysis at 800°C for 2 hours.
[0179] Analysis revealed that pyridine nitrogen accounted for 45.0% and the specific surface area was 780 m². 2 / g, sodium intercalation potential 1.46V, capacity retention 84.0% after 5000 cycles at 5C rate.
[0180] Comparative Example 3
[0181] This comparative example provides a negative electrode material.
[0182] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 2. In this comparative example, in step S200, the solid-liquid ratio between the lignin-free sisal fiber and water is 1:20.
[0183] Analysis showed that the pyridine nitrogen content was 53.6%, the sodium intercalation potential was 1.49V, and the capacity retention rate after 5000 cycles at 5C was 90.8%.
[0184] Comparative Example 4
[0185] This comparative example provides a negative electrode material.
[0186] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 2. In this comparative example, in step S200, the solid-liquid ratio between the lignin-free sisal fiber and water is 1:10, that is, the amount of water used is relatively small.
[0187] Analysis revealed that the pyridine nitrogen content was 47.8%, the sodium intercalation potential was 1.45V, and the capacity retention rate after 5000 cycles at 5C was 86.2%.
[0188] Comparative Example 5
[0189] This comparative example provides a negative electrode material.
[0190] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 2. In this comparative example, in step S200, the solid-liquid ratio between the lignin-free sisal fiber and water is 1:25, which means that the amount of water used is relatively large.
[0191] Analysis showed that the pyridine nitrogen content was 50.6%, the sodium intercalation potential was 1.47V, and the capacity retention rate after 5000 cycles at 5C was 88.7%.
[0192] Comparative Example 6
[0193] This comparative example provides a negative electrode material.
[0194] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 2. However, in this comparative example, the hydrothermal carbonization temperature in step S200 is 160°C, which is relatively low.
[0195] Analysis showed that the pyridine nitrogen content was 52.1%, the sodium intercalation potential was 1.49V, and the capacity retention rate after 5000 cycles at 5C was 91.4%.
[0196] Comparative Example 7
[0197] This comparative example provides a negative electrode material.
[0198] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 3. However, in step S400 of this comparative example, the second intermediate and 95wt% phosphoric acid were prepared in a mass ratio of 1:1.5, that is, the amount of phosphoric acid was relatively small.
[0199] Analysis showed that the pyridine nitrogen content was 49.5%, the sodium intercalation potential was 1.47V, and the capacity retention rate after 5000 cycles at 5C was 87.9%.
[0200] Comparative Example 8
[0201] This comparative example provides a negative electrode material.
[0202] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 3. In this comparative example, in step S400, the second intermediate and 95wt% phosphoric acid were prepared in a mass ratio of 1:2.5, that is, phosphoric acid was more abundant.
[0203] Analysis showed that the pyridine nitrogen content was 51.8%, the sodium intercalation potential was 1.48V, and the capacity retention rate after 5000 cycles at 5C was 89.5%.
[0204] Comparative Example 9
[0205] This comparative example provides a negative electrode material.
[0206] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 3. However, in step S500 of this comparative example, the third intermediate was placed in an atmosphere containing 4 vol% NH3, that is, the NH3 content was relatively low.
[0207] Analysis showed that the pyridine nitrogen content was 46.2%, the sodium intercalation potential was 1.45V, and the capacity retention rate after 5000 cycles at 5C was 85.6%.
[0208] Comparative Example 10
[0209] This comparative example provides a negative electrode material.
[0210] The negative electrode material of this comparative example was prepared using a preparation method that is basically the same as that of Example 3. However, in step S500 of this comparative example, the third intermediate was placed in an atmosphere containing 7 vol% NH3, that is, the NH3 content was relatively high.
[0211] Analysis showed that the pyridine nitrogen content was 54.2%, the sodium intercalation potential was 1.50V, and the capacity retention rate after 5000 cycles at 5C was 92.1%.
[0212] The relevant testing methods in this application are as follows:
[0213] 1. Structural testing: Weigh approximately 80 mg of the degassed carbon anode material sample and conduct N2 adsorption-desorption tests at liquid nitrogen temperature. Specific surface area is calculated using the BET method, pore size distribution is calculated using the DFT method, and volume percentage is calculated based on the pore volume distribution of micropores, mesopores, and macropores.
[0214] 2. Doping test: The N 1s spectrum was tested using XPS, with the binding energy range of 395eV~405eV. Peak fitting was used to obtain the proportions of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen. Five regions were selected on the same sample to test the total N and the proportion of pyridine nitrogen, and the relative standard deviation was calculated.
[0215] 3. Evaluation of doping uniformity: The N / C signal distribution is obtained by EDS surface scanning or XPS multi-point scanning, and the relative standard deviation of the N element signal is calculated; when RSD≤5%, the doping distribution is considered uniform.
[0216] 4. Preparation of negative electrode sheet: The carbon negative electrode material, conductive carbon black and CMC / SBR binder are mixed in deionized water at a mass ratio of 94:3:1.5:1.5, coated on the surface of copper foil, pre-dried at 80℃, vacuum dried at 120℃ for 12h, and then rolled and cut.
[0217] 5. Half-cell test: Using the obtained negative electrode as the working electrode and the sodium plate as the counter electrode, a half-cell was assembled using 1 mol / L Na2SO4 aqueous electrolyte. After standing at 25℃ for 6 h, constant current charge and discharge were performed, and the sodium intercalation potential at 0.1C, the capacity at 0.5C, and the capacity retention rate after 5000 cycles at 5C were recorded.
[0218] 6. GITT test: A test cycle consists of 10 min of pulse charge-discharge at a 0.5C rate followed by 40 min of rest. The sodium ion diffusion coefficient is calculated based on the voltage response curve.
[0219] The test results of Examples 1-3 and Comparative Examples 1-10 are shown in Table 1. Additionally, see [link to Table 1]. Figure 4 As shown, Figure 4 This is a comparison chart of the key performance of Examples 1 to 3 of this application with Comparative Examples 1 to 10.
[0220] Table 1
[0221]
[0222] The aforementioned carbon anode materials have at least the following beneficial effects:
[0223] (1) Voltage boost: Pyridine nitrogen induces a high sodium storage potential, with the potential reaching 1.52V~1.58V.
[0224] (2) Rapid diffusion: The gradient pores enable an ion diffusion coefficient of 5×10⁻⁶. -9 m 2 / s.
[0225] (3) High cycle life: 5C rate 5000 cycles capacity retention rate >95%.
[0226] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0227] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0228] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A carbon anode material, characterized in that, The carbon anode material has a porous structure, which includes micropores, mesopores, and macropores. The volume ratio of the micropores, mesopores, and macropores is (1.5~2):(2.5~2):
1. The pore size of the micropores is less than 2 nm, the pore size of the mesopores is 2 nm~50 nm, and the pore size of the macropores is greater than 50 nm. The total nitrogen content in the carbon anode material is 4 at%~5.5 at%, and the nitrogen content in pyridine nitrogen accounts for more than or equal to 55% of the total nitrogen content.
2. The carbon anode material according to claim 1, characterized in that, The specific surface area of the carbon anode material is 1000 m². 2 / g~1200m 2 / g.
3. A method for preparing a carbon anode material, characterized in that, Includes the following steps: Lignin removal treatment of sisal fibers; The sisal fibers after lignin removal treatment were subjected to hydrothermal carbonization to obtain a first intermediate. The first intermediate was subjected to oxygen-limited pyrolysis to obtain the second intermediate; The second intermediate was subjected to acid activation treatment to obtain the third intermediate; Furthermore, the third intermediate is subjected to nitrogen doping enhancement treatment.
4. The method for preparing the carbon anode material according to claim 3, characterized in that, The process of removing lignin from sisal fibers includes the following steps: The sisal fibers were placed in an alkaline solution and treated with alkali at a temperature of 80℃~100℃ for 2h~4h. The sisal fibers after alkali treatment are then washed with water. In addition, the sisal fibers after water washing are dried.
5. The method for preparing the carbon anode material according to claim 4, characterized in that, It also satisfies at least one of the following conditions: (1) The alkaline solution includes at least one of the following: 5wt%~8wt% NaOH solution, 5wt%~10wt% KOH solution, 3wt%~6wt% LiOH solution, 8wt%~12wt% Na2CO3 solution, 8wt%~12wt% K2CO3 solution, and 10wt%~20wt% ammonia water; (2) The water washing process meets the following conditions: the pH value of the aqueous solution containing the sisal fiber is 6.5~7.5; (3) The drying process meets the following conditions: the drying temperature is 60℃~70℃.
6. The method for preparing the carbon anode material according to any one of claims 3 to 5, characterized in that, It also satisfies at least one of the following conditions: (1) The hydrothermal carbonization treatment meets the following conditions: the solid-liquid ratio (g / mL) between the sisal fiber and water after lignin removal is 1:(15~20), the hydrothermal carbonization temperature is 180℃~220℃, and the hydrothermal carbonization time is 1h~3h; (2) The oxygen-limited pyrolysis treatment meets the following conditions: under a mixed atmosphere, the temperature is increased to 650℃~750℃ at a rate of 5℃ / min~10℃ / min, and the oxygen-limited pyrolysis time is 0.5h~2h. The mixed atmosphere includes oxygen and inert gas, wherein the concentration of oxygen is 0.5vol%~2vol%. Optionally, the inert gas flow rate is 50 mL / min to 60 mL / min; Optionally, the inert gas includes argon.
7. The method for preparing the carbon anode material according to any one of claims 3 to 5, characterized in that, It also satisfies at least one of the following conditions: (1) The acid in the acid activation treatment includes at least one of the following: 85wt%~95wt% phosphoric acid, 60wt%~75wt% sulfuric acid, 30wt%~65wt% nitric acid, 10wt%~20wt% hydrochloric acid, 20wt%~40wt% citric acid and 20wt%~40wt% p-toluenesulfonic acid; (2) The acid activation treatment meets the following conditions: the second intermediate and acid are mixed at a mass ratio of 1:(1.5~2.5) and activated in a protective atmosphere at a temperature of 850℃~950℃ for 20min~60min; (3) The nitrogen doping enhancement treatment meets the following conditions: the third intermediate is placed in an atmosphere containing 4 vol% to 6 vol% NH3 and microwaved for 5 min to 10 min under microwave power of 8 W / g to 12 W / g.
8. A negative electrode sheet, characterized in that, It includes at least one of the carbon anode materials according to any one of claims 1 to 2, and carbon anode materials prepared by the preparation method according to any one of claims 3 to 7.
9. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 8; Optionally, the secondary battery includes a sodium-ion battery.
10. An electrical device, characterized in that, The invention includes at least one of the following: the carbon anode material according to any one of claims 1 to 2, the carbon anode material prepared by the preparation method according to any one of claims 3 to 7, the anode sheet according to claim 8, and the secondary battery according to claim 9.